2018
DOI: 10.1111/ggi.13502
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and outcomes of accidental hypothermia among elderly patients in Japan: Data from the J‐Point registry

Abstract: Approximately 80% of patients with AH were aged ≥65 years. The in-hospital mortality rate of patients aged ≥65 years was significantly higher than that of those aged <65 years. Geriatr Gerontol Int 2018; 18: 1427-1432.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 15 publications
3
22
0
Order By: Relevance
“…Furthermore, some of the accidental hypothermia patients require invasive rewarming techniques, such as extracorporeal membrane oxygenation for hemodynamic support [ 1 3 ]. On the other hand, in a super-aging society such as Japan, most cases of accidental hypothermia occur in residential settings, and the patients are older, frail, and face difficulties in independent living [ 2 5 ]. Some patients in such a population might wish the withdrawal of ICU admission and invasive treatment for avoiding undesirable life-sustaining therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some of the accidental hypothermia patients require invasive rewarming techniques, such as extracorporeal membrane oxygenation for hemodynamic support [ 1 3 ]. On the other hand, in a super-aging society such as Japan, most cases of accidental hypothermia occur in residential settings, and the patients are older, frail, and face difficulties in independent living [ 2 5 ]. Some patients in such a population might wish the withdrawal of ICU admission and invasive treatment for avoiding undesirable life-sustaining therapy.…”
Section: Introductionmentioning
confidence: 99%
“…We found only 21 avalanche victims, who were the youngest group but the group with the highest mortality. Only the already mentioned study from the Netherlands and two recent studies from Japan discussed the issue of elderly people who suffered from accidental hypothermia [ 15 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The methodology of this study is reported in accordance with the Standards for Reporting of Diagnostic Accuracy Studies (STARD) 2015 guidelines [11]. This study was approved by the ethics committee of Kyoto University (R-1045).…”
Section: Methodsmentioning
confidence: 99%